Lifestyle changes in wild and veterinary isolates of Pseudomonas aeruginosa exposed to three veterinary care antibiotics - Jéssica Vieira Dantas; Hueliton Borchardt; Andrwey Augusto Galvão Viana; Rafael de Almeida Travassos; Ian Porto Gurgel do Amaral; Ulrich Vasconcelos (Revista Angolana de Ciências)
This study aimed to evaluate the planktonic and sessile activity of wild and veterinary Pseudomonas aeruginosa isolates exposed for 4 h to veterinary formulations composed of florfenicol (FLO) and sulfamethoxazole+trimethoprim (SXT), under different levels of Chemical Oxygen Demand (COD). Additional tests for pyocyanin production, antibiogram and cell wall hydrophobicity were performed. All isolates produced up to 3.26 µg/L of pyocyanin and had a strongly hydrophobic cell wall. Both the COD of 20,000 mg/L and the presence of FLO favored inhibition of cell adhesion by up to ≈45%, and no antibiofilm effect was found. FLO/SXT in concentrations 0.30/0.24 mg/mL exhibited greater activities. An increase of up to ≈16% was observed in the presence of FLO and lower percentages in the presence of SXT. There was a significant increase in planktonic cells by up to ≈32%. Two factors may have accounted for this: active detachment in the biofilm and duplication of tolerant cells, as swimming and running velocities were reduced but the cells remained viable (SXT > FLO). The results of the antibiogram indicated that veterinary isolates of P. aeruginosa were more sensitive to the antibiotics than wild isolates, however, in the in vitro biofilm formation test wild isolates were more susceptible to alteration than veterinary isolates. In the medium with a higher organic matter content, however, the switch from the sessile to the planktonic state seems to have served as a survival strategy for P. aeruginosa in subinhibitory concentrations of FLO and SXT.